STRATEGI PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PT. RIAU ANDALAN PULP AND PAPER DI KABUPATEN PELALAWAN - Aprilia Frastica Nainggolan; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Corporate Social Responsibility (CSR) program is now regarded as one of innovation in improving the welfare of society. This is done by community development activities that are sustainable. In accordance with Local Rule No. 6 year 2012 on Corporate Social Responsibility in Riau Province, there are still many companies that do not carry out its social responsibility to the community. This is because there are many companies who do not understand the importance of CSR as one of the roles in improving the welfare of society. But in PT. Riau Andalan Pulp and Paper is able to demonstrate success in implementing CSR programs, to gain an appreciation in income generation programs receiving communities. The purpose of this research was conducted to determine and analyze strategies for implementation of CSR programs, so that it can serve as guidelines for other companies in carrying out its social responsibility.In explaining the strategy of implementation at the company’s CSR program PT. RAPP, researches used Ellitan theory which includes: Technology Strategy, Innovation Strategy, Operations Strategy. This study used a qualitative descriptive method. Data was collected through interviews, observation, and collection of documents.The results show that the strategy of implementation of CSR programs in the RAPP is optimal. Since the implementation of the system has been integrated with a good strategy and provide a positive impact on the economic growth of poor beneficiaries.Key Words: Strategy, CSR programs, PT. Riau Andalan Pulp and Paper